Novel hydro- and lipo-philic selenium zinc(II) phthalocyanines: Synthesis, photophysical properties and photodynamic effects on CT26 colon carcinoma cells - Ezquerra Riega, Sergio Dario (2018)
The synthesis and photochemical properties of two novel selenium zinc(II) phthalocyanines, a lipid-soluble 2,9(10),16(17),23(24)-tetrakis [(2-dimethylamino)ethylselanyl]phthalocyaninato zinc(II) (4) and its water-soluble quaternized derivative 2,9(10),16(17),23(24)-tetrakis [(2- trimethylammonium)ethylselanyl]phthalocyaninato zinc(II) tetraiodide (5), were investigated. Maximum absorption values were 689 nm and 684 nm for 4 and 5 in DMF, respectively. In addition, phthalocyanines were revealed to be very efficient singlet oxygen generators with high values of ΦΔ 0.74 and 0.84 for 4 and 5 in DMF, and they were photostable over the irradiation times studied. The photodynamic effect were evaluated on CT26 colon carcinoma cells. After light exposure, 4 and 5 were found to be cytotoxic, and IC50 values were 0.5 ± 0.1 μM and 2.3 ± 0.6 μM, respectively. The production of a greater amount of reactive oxygen species after phthalocyanines irradiation would be responsible for its potent phototoxic action on CT26 colon carcinoma cells.